343 Phase 3 study of pembrolizumab + docetaxel and prednisone/prednisolone for metastatic castration-resistant prostate cancer (mCRPC) pretreated with next-generation hormonal agents (NHAs) (KEYNOTE-921). (9th November 2020) - Petrylak, Daniel; Shore, Neal; Bennamoun, Mostefa; Ratta, Raffaele; Piulats, Josep; Li, Ben; Schloss, Charles; Fizazi, Karim
Abstract : Background: Cohort B of the phase 1b/2 KEYNOTE-365 study (NCT02861573 ) found that docetaxel + pembrolizumab + prednisone demonstrated activity in patients previously treated with abiraterone acetate or enzalutamide for mCRPC. The prostate-specific antigen (PSA) response rate was 28%; objective response rate (ORR) was 18% (7 partial responses); duration of response (DOR) was 6.7 months; progression-free survival (PFS) was 8.3 months; overall survival (OS) was 20.4 months; and the 12-month PFS and OS rates were 24.0% and 75.8%, respectively. The safety and tolerability profile of this combination was consistent with the profiles of each individual agent. The KEYNOTE-921 (NCT03834506 ) phase 3 trial will evaluate efficacy and safety of pembrolizumab + docetaxel + prednisone/prednisolone in patients with mCRPC after prior treatment with NHA. Methods: Eligible patients are adults with histologically or cytologically confirmed mCRPC who experience disease progression with androgen deprivation therapy (or after bilateral orchiectomy) within 6 months of screening and have Eastern Cooperative Oncology Group performance status 0/1. Other eligibility criteria are disease progression or intolerance to NHA in the metastatic hormone-sensitive prostate cancer setting or CRPC setting, no prior treatment with chemotherapy for mCRPC, and tissue available for biomarker analysis. Treatment stratification factors are prior treatment with abiraterone acetate (yes or no) and metastases location (bone only, liver, other). Approximately 1000 patients will be randomly assigned to receive docetaxel 75 mg/m2 IV Q3W + prednisone/prednisolone 5 mg orally BID and pembrolizumab 200 mg IV Q3W or docetaxel 75 mg/m2 IV Q3W + prednisone/prednisolone 5 mg PO BID + placebo IV Q3W (1:1 ratio). Response and progression will be determined using imaging (CT/MRI/bone) according to PCWG3–modified RECIST v1.1 by blinded independent central review (BICR) Q9W during the first year and Q12W thereafter. Treatment maximums are 10 cycles for docetaxel + prednisone/prednisolone and 35 cycles for pembrolizumab or placebo. Treatment discontinuation regardless of therapy received is mandated for disease progression, unacceptable toxicity, or consent withdrawal. The dual primary end points are radiographic PFS per PCWG3-modified RECIST v1.1, as assessed by BICR and OS, and the key secondary end point is time to initiation of subsequent anticancer therapy or death. Other secondary end points include PSA response rate, time to PSA progression, ORR, DOR, time to radiographic soft tissue progression, time to radiographic bone progression, and safety. KEYNOTE-921 is ongoing or planned in 22 countries across, Asia, Australia, Europe, and North and South America. Results: N/A Conclusions: N/A Ethics Approval: The study and the protocol were approved by the Institutional Review Board or ethics committee at each site.